(untitled) - Clancy, Tom; Cameron, Marc (New York, 2019)
"As President of the United States, Jack Ryan has faced many challenges, but none have been as personal as this and never has he been this helpless in the face of evil in the latest entry in Tom Clancys #1 New York Times bestselling series"--
Keywords: Ryan, Jack; Sr. (Fictitious character); Fiction; Suspense fiction